CREATIVE PEOPLE AND THE DEVELOPMENT OF SUPERIOR CAPTURE FISHERY PRODUCTS IN SAMOTA - Santi Nururly; Abdul Azis Bagis; Burhanudin; Riska Sakinah (RADJA PUBLIKA, 2026)
This study aims to analyze the role of creative individuals in the development of superior captured fish products in Teluk Santong Village, SAMOTA area, Sumbawa Regency. Human resource creativity is an important factor in increasing the added value of fishery products through product innovation and business management. This associative study involved 97 respondents consisting of fishermen who had participated in product development training activities. Data were collected through questionnaires and processed using Smart Partial Least Square (SmartPLS) software to test the relationship between variables. Creative individuals were the independent variable, while the dependent variable was the development of superior products, with training as a medium for capacity building. The results showed that the creativity of capture fishermen had a positive and significant influence on the development of superior products through training. This means that the higher the level of creativity possessed by fishermen, especially after participating in training, the greater their ability to develop products based on captured fish with higher economic value and competitiveness. This finding confirms that the development of creative individuals is a key factor in driving local economic transformation based on marine and fisheries potential. Therefore, the sustainability of creativity-based training and mentoring programs needs to be strengthened to encourage the creation of sustainable superior product innovation in the SAMOTA area.